(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Intoxication of chocolate for small-animals may be threatening to life and associated with serious morbidity and mortality. This study was aims to compares the effect of dark cocoa ingestion in rabbits, local dogs and breeds dogs. The animals were randomly (4 rabbits or dogs/group) divided into two groups which include: Group- I (control group) was feed on normal diet, Group-II (G-treated) was feed on diet with 250 mg/Kg BW of dark cocoa (for 2 weeks to rabbits and 4 weeks for local dogs) while in breed dogs, While the serum and data of breed dogs taken from Veterinary Clinics. The results of clinical signs different in duration of occurrence intoxication between the animals used in this experiment, it more significantly effect in breed dogs and then male rabbits. Lier enzymes and oxidative enzymes elevation in rabbits after two weeks and four weeks in local dogs while in the breed dogs elevation within two days after ingestion of dark cocoa also significantly increased in lipid profile except HDL in all groups of treated in compared to the control groups also total protein, urea and creatinine elevation in all groups of ingestion cocoa with different duration of occurrence of intoxication. The current public presentation will focus on the latest findings on the effects of dark cocoa, its major constituents, and cocoa derivatives on selected biomarkers of toxicity and its duration in rabbits and dogs.